Counting on a cool Tokyo summer. - Boyd, J. (IEEE spectrum)
Tokyo faces a danger more commonly associated with Third World countries: summertime electricity blackouts. The situation is so precarious that the Tokyo Electric Power Co. Inc. (Tepco) has launched a high-profile ad campaign exhorting its customers to conserve energy. Japan's leading utility is urging its customers to conserve. Tokyo's power crisis originated in a big safety and oversight scandal that forced Tepco to close down its 17 nuclear reactors for inspection. Nuclear power generation accounts for 17 GW of Tepco's total capacity of 59 GW, which supplies 40 percent of the Tokyo metropolitan power needs and 27 million customers. With summer fast approaching, Tepco employees and NISA officials are busy meeting with residents near the plants to convince them that the reactors will indeed be safe to restart. Tepco has been scrambling to buy electric power from other utility companies and reactivate some thermal power plants. The government's conservation campaign includes a request to industry to advance the summer "Obon" holiday from mid-August to the end of July or early August, when electricity demand is highest. Consumers are being asked to set their air-conditioner thermostats at a higher-than-usual 28 °C.